The Supporting of Schemata as Integrated Strategy in Reading Literacy: A Qualitative Study - Saepudin, Aep; Umisara, Elinda (Universitas Negeri Semarang, 2020)
The schemata are conceptual frameworks that are in the form of design process for translating the particular idea, where the reading activities require the proper scheme in understanding the information. The students read with traditional technique that has not yet to build the perspective information. There should be an evaluation of the strategy for integrating information, so the purpose of this research provides an overview of how the schemata role integrating the students reading literacy. The population of this research is the student in eighth grade at SMPN 1 Lebakwangi. This method of research is qualitative descriptive with case study design. The results show the potential schemata providing the significance in students’ reading literacy, where students can identify the information, synthesize information and facilitate information. Three stages use for generating information based on the perspective built through the schemata stages. The implications of this study provide an insight into concept mapping information in reading literacy. There are schemata as strategy to divide information based on the questions and make summarization. It takes the students to convey information becoming a critical reader by eliminating inappropriate information.